2016
DOI: 10.4103/0974-7796.164854
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration in the renal function and risk of microalbuminuria after radical, simple and donor nephrectomy: A long-term outcome

Abstract: Objectives:Evaluation of deterioration in renal function and risk of micro albuminuria after radical, simple and donor nephrectomy.Materials and Methods:A total of 594 patients underwent nephrectomy (159 radical, 318 simple and 117 donors) from February 2009 to December 2012 in our institute. First 300 eligible patients were divided in 3 groups, each having equalled number of patients. Group 1 was consisted of patients who underwent radical, group 2 had simple and group 3 had donor nephrectomy. These patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…12,13,14 However, in developed countries where imaging modality is frequently performed, incidental RCC burden is more and is up to 50% of cases. 15 While our study reported 40% incidental cases close to those presented in western literature. Incidental cases are uncommon in developing countries partly because of the low availability of imaging modalities and late presentation to hospitals with severe symptoms of a particular disease.…”
Section: Discussionsupporting
confidence: 76%
“…12,13,14 However, in developed countries where imaging modality is frequently performed, incidental RCC burden is more and is up to 50% of cases. 15 While our study reported 40% incidental cases close to those presented in western literature. Incidental cases are uncommon in developing countries partly because of the low availability of imaging modalities and late presentation to hospitals with severe symptoms of a particular disease.…”
Section: Discussionsupporting
confidence: 76%
“…Consistent with our study, they reported that patients undergoing LRN were older, had a higher frequency of comorbid diseases, and experienced a higher frequency and severity of chronic kidney disease postoperatively. The best results were reported in the LDN group [17]. In another study evaluating the effect of all 3 laparoscopic nephrectomy techniques on health-related quality of life, Wiesenthal et al reported that patients undergoing LRN were significantly older than the other 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…After two years of follow-up, the difference in GFR was found to be significant between RN and SN, or RN and DN. At postoperative 6th years, while 41.6% of patients in RN group and 8.6% of patients in SN group developed stage 3 CKD, only 3 patients in DN group developed stage 1 CKD (Verma et al, 2016).…”
Section: Discussionmentioning
confidence: 99%